Multifocality in patients treated for papillary Thyroid Carcinoma: a preliminary analysis of related risk factors. - Del Rio, Paolo; Loderer, Tommaso; Giuffrida, Mario; Cozzani, Federico; Rossini, Matteo; Bonfili, Deborah; Bonati, Elena (Acta Biomedica Atenei Parmensis, 2021)
BackgroundMultifocality is usually detected afterwards surgery for papillary thyroid cancer (PTC) and has been reported in 18-87% of PTC. MethodsThis is a retrospective single-center study involving a series of 238 patients that underwent thyroidectomy or lobectomy after preoperative fine needle aspiration (FNA) diagnosis of Thyr 5 or Thyr 6, according to Bethesda classification, from January 2015 to December 2019 at the General Surgery Unit of the University - Hospital of Parma. We divided patients into two main groups: patients with multifocal papillary thyroid cancer at postoperative diagnosis and patients with unifocal papillary thyroid cancer. The aim of the study is to identify demographic or preoperative radiological risk factors for the presence of multifocal PTC and to verify the presence of cyto-histological features of greater aggressiveness in multifocal tumors than in unifocal ones.ResultsOut of our sample, 176 patients were females (73,9%) and 62 males (26,1%) with a mean age of 50,45 ±14,41. Preoperative cytological diagnosis resulted Thyr 5 in 47 cases (19,7%) and Thyr 6 in 191 cases (80,3%). Multifocal cancer was reported in 35,8% of the females and in 32,3% of the males. Older age was significatively related to the presence of multifocal papillary carcinoma (p